Withaferin A Suppresses Beta Amyloid in APP Expressing Cells: Studies for Tat and Cocaine Associated Neurological Dysfunctions - Tiwari, Sneham; Atluri, Venkata Subba Rao; Yndart Arias, Adriana; Jayant, Rahul Dev; Kaushik, Ajeet; Geiger, Jonathan; Nair, Madhavan N. (Frontiers in Aging Neuroscience, 2018)
Neurological disorders are the biggest concern globally. Out of ~36 million HIV positive people about 30-60% exhibit neurological disorders including dementia and Alzheimer’s disease (AD) like pathology are on top of the list. In AD or AD like neurological disorders, the pathogenesis is mainly due to the abnormal accumulation of extracellular amyloid beta (Aβ). In this era of antiretroviral therapy, the life span of the HIV-infected individuals have increased leading towards increased neurocognitive dysfunction in nearly 30% of HIV-infected individuals, specifically older people. Deposition of the amyloid-β (Aβ) plaques in the CNS is one the major phenomenon happening in ageing HIV patients. ART suppresses the viral replication, but the neurotoxic protein (Tat) is still produced and results in increased levels of Aβ. Furthermore, drugs of abuse like cocaine (coc) is known to induce the HIV associated neurocognitive disorders as well as the Aβ secretion. To target the Tat and coc induced Aβ secretion, we propose a potent bifunctional molecule Withaferin A (WA) which may act as a neuro-protectant against Aβ neurotoxicity. In this study, we show that WA reduces secreted Aβ and induced neurotoxicity in APP-plasmid transfected SH-SY5Y cells (SH-APP). In this, study we show that in SH-APP cells, Aβ secretion is induced in the presence of HIV-1 Tat (neurotoxic) and drug of abuse coc. Our Fluorescent microscopy studies show the increased concentration of Aβ40 in Tat (50ng/ml) and coc (0.1μM) treated SH-APP cells as compared to control. Our dose optimization study show, lower concentrations (0.5-2μM) of WA significantly reduce the Aβ40 levels, without inducing cytotoxicity in the SHAPP cells. Additionally, WA reduces the Tat and cocaine induced Aβ levels. Therefore, we propose that Aβ aggregation is induced by the presence of Tat and coc and WA is potent in reducing the secreted Aβ and induced neurotoxicity. Our study provides new opportunities for exploring the pathophysiology and targeting the neurological disorders.